AKTIVITAS KOMUNIKASI PEMASARAN HOTEL GRAND DAFFAM BELA TERNATE - Cici Aryansi Quilim (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Bela International Hotel is the only five-star hotel in Ternate where in deal with competition between hotels, it is necessary to provide specific and innovative facilities and services to be superior to its competitors. Competitive competition in the hospitality world at this time encourages every hotel to create a promotional program offered to hotel guests. Thus, the function and role of strategic marketing communication is needed so that positive information about the hotel can be received by the public so that in the end the community makes the hotel as a choice. Marketing communication activities carried out by paying attention to two aspects namely; internal and external marketing communication. With the concept of integrated marketing communication, it is not enough to depend on just one material, so that Bela International Hotel combines the concept of marketing with customer relations and maintenance services.